New pharmacological possibilities for the treatment of schizophrenia: an integrative literature review (Research, Society and Development, 2022)
Introduction: in people affected by schizophrenia, almost half of the patients who make the correct use of the medication still suffer from the manifestations of the disease, since the antipsychotics currently available on the market only alleviate the presentation and recurrence of most symptoms, but not all. they. Objective: to observe Brazilian research in what permeates the country's pharmacological development, which is of extreme relevance to the population as a whole. Methodology: this is a descriptive research of the integrative literature review type, carried out through online access to the National Scientific Electronic Library Online (Scielo), Google Scholar and EBSCO Information Services databases, in March and April 2022. Results and discussion: there are several effects of antipsychotics in the different stages of schizophrenia, and this group of drugs reduces psychotic symptoms in addition to improving mood and reducing sleep disturbances. They are divided into two groups: typical and atypical – they are differentiated according to the occurrence of adverse effects. These include ascorbic acid, Erythrina velutin, alpha-lipoic acid, beta-caryophyllene, Paliperidone Palmitate, Aripiprazole, lumateperone, cannabidiol. Final considerations: in animal studies, ascorbic acid supplementation was effective in preventing oxidative damage and sensorimotor loss, and beta-caryophyllene had an antipsychotic effect and reversed behavioral changes; it is of interest to do human studies to see if these effects can be reproduced in people. Alpha-lipoic acid can be used as adjunctive therapy to atypical antipsychotics causing a reduction in negative symptoms and psychomotor agitation and improvement in cognitive functions. Aripiprazole is a good alternative for obese patients or patients with metabolic disorders, however, it has a higher financial cost. Lumateperone is an option for the comprehensive treatment of schizophrenia.